Pengaruh intellectual capital terhadap financial performance pada perusahaan non-family business - Kezia Josephine; Vianty Adella Santo; Cecilia Aura Chantika (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2023)
The purpose of this study is to conduct an influence test and provide empirical evidence of the influence of independent variables, namely Intellectual Capital on dependent influences, namely Financial Performance which is assessed using ROA (Y1) and ROE (Y2) on non-family business companies. This study then applies multiple regression analysis which includes classical assumption tests, hypothesis tests and descriptive statistical tests. Data testing is assisted by using the SPSS program. The total number of companies consistently recorded in Kompas100 during 2018 – 2021 is 141 companies, but the number of samples that comply with purposive sampling provisions is 45 companies. Thus, the observation data used amounted to 158 research data. The results prove that IC has a positive influence on ROE and ROA. While firm's size has a significant negative effect on ROE and ROA. Public interest statements This research can be used as input in the assessment carried out by company management and the general public to measure the company's financial performance. The factors in this assessment can be seen through the development of intellectual capital by companies that do not only focus on tangible assets, but also manage their intangible assets.